Untangling the Web: Exploring the Impact of GDP Per Capita and Corruption Levels on CO2 Emissions - A Comparative Analysis Across Nations and within ASEAN - Suryanto, Edy; Ratnasari, Dwi; Kurniawan, Agus Nur Ikhsan (Jurnal Ekonomi Pembangunan, 2024)
Environmental pollution and climate change have severely threatened human health and ecosystems. This study seeks to examine the effect of GDP Per Capita and the level of corruption on CO2 emissions with two focuses, namely by country and by ASEAN members. The approach used is the panel data regression model with the Eviews analysis tool. Secondary data in the form of panel data is used in this study with a time duration of 2012 to 2018 (time series) in six countries (cross-section). The results showed no differences in the determinants that affected CO2 emissions in both republics and kingdoms. Meanwhile, according to the ASEAN region, it was found that GDP Per Capita and the level of corruption affected CO2 Emissions. This study suggests that the government needs to enforce policies and implement corruption sanctions in accordance with applicable procedures and formulate and implement policies in accordance with sustainable development by considering all forms of policies that support economic growth